Peripheral Blood Lymphocyte Subsets Predict the Efficacy of Immune Checkpoint Inhibitors in Non–Small Cell Lung Cancer - Miao, Kang; Zhang, Xiaotong; Wang, Hanping; Si, Xiaoyan; Ni, Jun; Zhong, Wei; Zhao, Jing; Xu, Yan; Chen, Minjiang; Pan, Ruili; Wang, Mengzhao; Zhang, Li (Frontiers in Immunology, 2022)
Background Non–small cell lung cancer (NSCLC) has entered the era of immunotherapy. However, only partial patients were able to benefit from immune checkpoint inhibitors (ICIs). Currently, biomarkers for predicting patients’ response to ICIs are primarily tumor tissue dependent and have limited accuracy. There is an urgent need to explore peripheral blood-based biomarkers to predict the efficacy and safety of ICI therapy. Methods To explore the correlation between lymphocyte subsets and the efficacy and safety of ICIs, we retrospectively analyzed peripheral blood lymphocyte subsets and survival prognosis data of 136 patients with stage IV NSCLC treated with ICIs. Results The two factors that had the greatest impact on the prognosis of patients with NSCLC treated with ICIs were CD4+CD45RA− T cell (HR = 0.644, P = 0.047) and CD8+ T/lymphocyte (%) (HR = 1.806, P = 0.015). CD4+CD45RA− T cell showed excellent predictive efficacy (AUC = 0.854) for ICIs monotherapy, with a sensitivity of 75.0% and specificity of 91.7% using CD4+CD45RA− T cell >311.3 × 106/L as the threshold. In contrast, CD8+ T/lymphocyte (%) was only associated with the prognosis but had no predictive role for ICI efficacy. CD4+ T cell and its subsets were significantly higher in patients with mild (grades 1–2) immune-related adverse events (irAEs) than those without irAEs. CD8+CD38+ T cell was associated with total irAEs and severe (grades 3–4) irAEs but was not suitable to be a predictive biomarker. Conclusion Peripheral blood CD4+CD45RA− T cell was associated with the prognosis of patients with NSCLC applying ICIs, whereas CD8+CD38+ T cell was associated with irAEs and severe irAEs.